Enzymatic synthesis of galactosylkojic acid with immobilized β-galactosidase from bacillus circulans - Ali Hassan, Mohd.; Ismail, Fadhilah; Yamamoto, Shuichi; Yamada, Hidenori; Nakanishi, Kazuhiro (Taylor & Francis Group LLC, 1995)
Galactosylkojic acid, in which the hydroxymethyl group of the kojic acid moiety is β-galactosylated, was synthesized by using a transgalactosidation reaction with an immobilized β-galactosidase from Bacillus circulans. With 5% kojic acid and 20% lactose as the substrates, the yield with respect to the initial amount of kojic acid was around 24% as a maximum. The inhibitory effect of galactosylkojic acid towards the oxidation reaction of L-β-(3,4-dihydroxyphenyl)alanine (L-DOPA) with tyrosinase was similar to that of kojic acid.